(untitled) (Journal of Contemporary Philology, 2020)
This paper explores the puns in Lewis Carroll’s Alice in Wonderland, with a special focus on their types, as well as their Macedonian equivalents. Its aim is to discover on which linguistic techniques the puns are based on, and to present the varieties of their Macedonian translations – where they differ, where they are similar, which techniques are used by the translators, and whether the translations are ‘successful’. This is achieved through a comparative analysis of the original puns and their six translation varieties in Macedonian. Besides comparing the original with its translation varieties, the author provides a comparison between the translation varieties as well, highlighting the strategies used by the translators and comparing the variations based on their preferred translation strategy. The findings reveal that the focus of the majority of the translators is mainly on the recreation of the puns by using creative linguistic solutions. Otherwise, the result is an incoherent piece of text, which neither the readers nor the translators themselves can comprehend.